Effects of Harvest Time on Quality of Stored Maize (Zea mays L.) in the Southern Part of Ghana - Asare, Sharon Gyekyewaa (2023)
In Ghana, most smallholder maize farmers delay harvesting of their crops in an attempt to achieve optimum moisture content levels necessary for safe storage. Late harvesting may cause a hike in insect attacks and fungal contaminations, leading to alterations in nutrient composition of grains. This study examined the effects of harvest time and storage form on quality of maize. Maize was grown and harvested from 36 plots, with each plot measuring 3m x 3m. Planting of maize was done during the major and minor seasons (April – August, 2020 and September – December, 2020) respectively. Moisture content of maize before storage was determined as 12.50 % to 12.85 % (major season) and 11.90 % to 12.48% (minor season). Harvesting was done at three stages (E = Early harvest, M = Mid harvest and L = Late harvest) and maize was stored for 90 days in three different ways (D = Dehusked, H = Husked and S = Shelled). Data was subjected to Analysis of variance (ANOVA) using Sisvar version 5.6. Mid harvest dehusked maize had the highest final starch content (69.28 %) while Early harvest husked maize had the highest protein content (7.22 %). Ash content of maize from the various treatments ranged from 3.50% to 5.39 % (initial) and 3.03 % to 4.13 % (final), the difference was significant (p<0.05). Late harvest husked maize (LHH) recorded 35 % more initial ash as compared to EHS. Aflatoxin level was highest on Late harvest dehusked maize (60.70 ppb). Nutrient and aflatoxin levels of maize were significantly affected by harvest time. Encouraging farmers to adopt a better approach to harvesting, drying and storage of maize can reduce crop losses and ensure food security.